NEPOTISM IN INDONESIA: A LOOK AT RATU ATUT'S POLITICAL DYNASTY IN BANTEN - Suramahardini, Karima Mahesa; Erawan, I Ketut Putra; Noak , Piers Andreas (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Nepotism in Indonesia: the political footprint of Ratu Atut dynasty in Banten. Dynastic politics is an attempt to divide the office to relatives themselves, common among the elite who hold power, given to relatives in order to maintain power with a specific purpose. In a democratic country, of course dynastic politics is the enemy that must be staged. Dynastic politics emerged and existed due to the growth of neopatrimonialism in Indonesia. Julius Cesar Imperial Trajono, he said that the dynastic politics that occurred in the regions in Indonesia was due to the weak institutional system of the party. Ratu Atut's case in Banten. Starting from his father, Tubagus Chasan Sochib who is famous for his influence in Banten, he delivered Djoko Munandar and his son Ratu Atut as The Governors-Vice Governors of Banten in 2001 which in the end Ratu Atut succeeded in becoming the second Governor of Banten Province and became the first female governor in Indonesia. Since the establishment of Banten, Ratu Atut has been a deputy governor once, and twice as governor of Banten. Atut abused her authority, she made changes to the budget of APBD and APBDP related to the procurement of medical devices in Banten.